Early Activation of iNKT Cells Increased Survival Time of BALB/c Mice in a Murine Model of Melioidosis - Kasetthat T. (2023)
Melioidosis is an infectious disease caused by Burkholderia pseudomallei. High interferon gamma (IFN-γ) levels in naive mice were reported to mediate protection against B. pseudomallei infection. Invariant natural killer T (iNKT) cells can produce and secrete several cytokines, including IFN-γ. When iNKT cell-knockout (KO) BALB/c mice were infected with B. pseudomallei, their survival time was significantly shorter than wild-type mice. Naive BALB/c mice pretreated intraperitoneally with α-galactosylceramide (α-GalCer), an iNKT cell activator, 24 h before infection demonstrated 62.5% survival at the early stage, with prolonged survival time compared to nonpretreated infected control mice (14 ± 1 days versus 6 ± 1 days, respectively). At 4 h after injection with α-GalCer, treated mice showed significantly higher levels of serum IFN-γ, interleukin-4 (IL-4), IL-10, and IL-12 than control mice. Interestingly, the IFN-γ levels in the α-GalCer-pretreated group were decreased at 4, 24, and 48 h after infection, while they were highly increased in the control group. At 24 h postinfection in the α-GalCer group, bacterial loads were significantly lower in blood (no growth and 1,780.00 6 51.21, P < 0.0001), spleens (no growth and 34,300 ± 1,106.04, P < 0.0001), and livers (1,550 ± 68.72 and 13,400 ± 1,066.67, P < 0.0001) than in the control group, but not in the lungs (15,300 ± 761.10 and 1,320 ± 41.63, P < 0.0001), and almost all were negative at 48 h postinfection. This study for the first time shows that early activation of iNKT cells by a-GalCer helps clearance of B. pseudomallei and prolongs mouse survival.